A Group Decision Process for Resource Allocation in the Health Setting - Nackel, John G.; Goldman, Jay; Fairman, William L. (Management Science, 1978)
A group decision process is developed that allocates an available budget to health programs based on program effectiveness. The program effectiveness is measured by comparing alternative programs (at various funding levels) with respect to the weighted objectives of the health care organization. The organizational objectives are weighted by a constant-sum paired comparisons scaling technique. An integer programming formulation allows the decision makers to maximize program effectiveness within the given budgetary, resource, regulatory, and program structure constraints. The Effectiveness Evaluation-Resource Allocation Process (ERAP) is validated by actual decision making teams testing four processes for resource allocation. An example from the validation experiment is presented to demonstrate the process.